(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
A novel nerve repairing material PRGD/PDLLA/03b2-TCP was synthesized and characterized with Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR) spectroscopy, and mass loss ratio. The effects of PDLLA or PRGD/PDLLA/03b2-TCP on viability and growth of Schwann Cells (SCs) were investigated by MTT assay and SEM. After implantation of different materials, histological assessment was performed. The results showed that, compared with PDLLA, PRGD/PDLLA/03b2-TCP materials displayed better biocompatibility, degradation property and less inflammatory reaction. Moreover, PRGD/PDLLA/03b2-TCP materials promoted the adhesion and proliferation of Schwann cells and exhibited better degradation performance than pure PDLLA. These results indicated that PRGD/ PDLLA/03b2-TCP has a potential application in the fields of nerve regeneration.